2018
DOI: 10.1002/suco.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and physical behavior of cement paste and mortar incorporating nano‐CaO

Abstract: The aim of this work is to experimentally investigate the effect of properties of nano-CaO in cement-based materials. Mortars and paste samples were produced by using nano-CaO in 2.5, 5, and 7.5% ratios instead of cement. The initial and final setting times and volumetric autogenous shrinkage tests of paste samples and 7, 28, and 360 days' compressive strength, the ultrasonic pulse velocity, heat of hydration, and linear autogenous shrinkage of mortar samples were determined. In addition, the micro-structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…From the 15%, 20%, and 25% blended CM cement, partial voids could be observed, which reduced the durability. as well as in the anhydrate parts of the cement grains [52,53]. It was found that the microstructure of OPC and 5% and 10% CMW mix after 7 and 28 days of hydration formed poor crystalline particles of tobermorite-like CSH phases that were indulged, as well as the remaining anhydrate parts of cement and CMW grains.…”
Section: Water Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 15%, 20%, and 25% blended CM cement, partial voids could be observed, which reduced the durability. as well as in the anhydrate parts of the cement grains [52,53]. It was found that the microstructure of OPC and 5% and 10% CMW mix after 7 and 28 days of hydration formed poor crystalline particles of tobermorite-like CSH phases that were indulged, as well as the remaining anhydrate parts of cement and CMW grains.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Microstructure Analysis After a Fracture Figure 6 provides the morphology of hydrated pristine OPC paste after 28 days. The SEM micrograph shows the formation of amorphous and microcrystalline phases of tobermorite-like hydrated products such as calcium silicate hydrate (CSH), along with calcium aluminate hydrates, and hexagonal calcium hydroxide; these hydrates are deposited in the originally water-filled spaces as well as in the anhydrate parts of the cement grains [52,53]. It was found that the microstructure of OPC and 5% and 10% CMW mix after 7 and 28 days of hydration formed poor crystalline particles of tobermorite-like CSH phases that were indulged, as well as the remaining anhydrate parts of cement and CMW grains.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Calcium oxide (CaO) is also used as an additive in mortars and concretes in percentages of up to 5% to reduce shrinkage without adverse effects on compressive strength in high-performance concrete. This is due to its pozzolanic effect when used in combination with silica fume [33].…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Firstly, there is a slight improvement in packing produced by GCW-GS, as can be seen in the granulometric curves in Figure 3. Secondly, the presence of Fe2O3 and CaO in the mixture improves pozzolanic activity [29], [30], [31], [32] and reduces autogenous shrinkage [33]. The favourable effect of Fe2O3 occurs for substitution percentages of around 2-3% on the total quantity of cement [31], [34].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Yüksek kimyasal aktivite ve erken yaş yüksek hidratasyon ısısına sahip olan nano-CaO'in hem bu özellikleri hem de puzolanik reaksiyonu sayesinde erken yaş basınç dayanımını artırdığı bilinmektedir (Sun et al 2020). Ayrıca, Polat et al tarafından suyla reaksiyonu sonucunda (Ca(OH)2 oluşumu) %93 civarında hacim genleşmesinden dolayı otojen rötreyi azalttığı ifade edilmiştir (Polat et al 2019). Hakamy and Shaikh (2015), nano kil partiküllerinin nanokompozit çimento hamurlarının fiziko-mekanik ve termal özelliklerini geliştirdiğini ifade etmişlerdir.…”
Section: Introductionunclassified